2020
DOI: 10.1097/crd.0000000000000355
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterium Jeikeium Endocarditis

Abstract: Corynebacterium jeikeium is a gram-positive, aerobic, pleomorphic, nonspore forming bacillus, commonly present on the skin surface. Infective endocarditis secondary to C. jeikeium most commonly affects leftsided heart valves and has a higher likelihood to require valve replacement compared to other Corynebacterium endocarditis. C. jeikeium endocarditis is extremely difficult to treat as it is characteristically resistant to penicillin, cephalosporins and aminoglycosides, and sensitivity to quinolones, macrolid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…The genus Corynebacterium could be part of the human commensal flora that may or may not be responsible for bacteremia in an opportunistic manner. While this genus includes the agent responsible for diphtheria ( Corynebacterium diphteriae complex, responsible for a potentially fatal infection caused by this toxigenic strain) and while C. jeikeium and C. urealyticum are involved mainly in bacteremia and urinary tract infections, C. gottingense has been reported in only one case of bacteremia [ 15 , 16 , 17 , 18 ]. The context of the infection has not been described in the clinical data either.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Corynebacterium could be part of the human commensal flora that may or may not be responsible for bacteremia in an opportunistic manner. While this genus includes the agent responsible for diphtheria ( Corynebacterium diphteriae complex, responsible for a potentially fatal infection caused by this toxigenic strain) and while C. jeikeium and C. urealyticum are involved mainly in bacteremia and urinary tract infections, C. gottingense has been reported in only one case of bacteremia [ 15 , 16 , 17 , 18 ]. The context of the infection has not been described in the clinical data either.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies Corynebacterium spp. have been associated with CIED-associated endocarditis [7,8,[11][12][13][14][15]. In a study examining 30 IE episodes due to Corynebacterium spp., the median age of the patients was 71 years and 77% of them were male.…”
Section: Discussionmentioning
confidence: 99%
“…In a study examining 30 IE episodes due to Corynebacterium spp., the median age of the patients was 71 years and 77% of them were male. C. striatum (n=11) and C. jeikeium (n=5) were the most common species [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,7,[11][12][13][14][15][16] There are also increasing reports on non-diphtheriae Corynebacterium-related UTIs, but most studies were case reports or focused on one species only. 8,14,[17][18][19][20][21] Very few studies have identified non-diphtheriae Corynebacterium involving infections at the species level. 13,22 The increase of clinical relevance, unpredictable antimicrobial susceptibilities to the currently available agents, as well as little understanding of potential drug resistance mechanisms all make it necessary to move forward in this line of research.…”
Section: Introductionmentioning
confidence: 99%